Unraveling the Multilevel Dynamics of Water, Sanitation, and Child Anthropometry in Indonesia - Kirana, Rifa; Komarulzaman, Ahmad (Makara Journal of Health Research, 2024)
Background: Anthropometrics, reflecting nutritional status, growth, and development, are crucial elements that can predict a person’s health and well-being. However, low anthropometric measures among children under 5 years remain a significant issue in Indonesia, often influenced by various factors at the household and community levels. Access to clean water and adequate sanitation has been identified as major determinants of these adverse health outcomes. This study analyzes the relationship between anthropometric measures and access to water and sanitation at household and community levels using a multilevel analysis approach. Methods: The study employs cross-sectional data from the Indonesian Family Life Survey (IFLS) waves 4 (2007) and 5 (2014), comprising a combined sample of 7,583 children. Furthermore, height-for-age z-scores (HAZ) and weight-for-height z-scores (WHZ) serve as the dependent variables, while improved water and sanitation access are the main independent variables. To account for the hierarchical nature of the data, a multilevel linear regression model is employed, clustering individuals, households, and communities at various levels. Results: The results indicate that improved sanitation at the household level and water coverage at the community level are significantly associated with higher HAZ, increasing the scores by 0.171 standard deviation (SD) (p < 0.01) and 0.004 SD (p < 0.1), respectively. However, the water and sanitation variables do not reveal a significant association with WHZ. Conclusions: The results of the study emphasize the importance of household-level sanitation and community-level water sources in influencing children’s health. Effective interventions must target improvements in water and sanitation facilities at household and community levels simultaneously to enhance children’s health and well-being. Recognizing and addressing the contextual factors at multiple levels is crucial for developing comprehensive health strategies.